2021
DOI: 10.1155/2021/5582697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar and Inorganic Fertilizer on the Soil Properties and Growth and Yield of Onion (Allium cepa) in Tropical Ethiopia

Abstract: Biochar is a carbon-rich product, which is processed by pyrolyzing biomass to improve soil properties and maintain environmental sustainability. This study aim was to investigate the effect of biochar and inorganic fertilizer on soil properties, growth, and yield. Four treatments and four replications have been used for the experimental plots using Randomized Complete Block Design (RCBD). Soil physiochemical properties have been investigated based on soil samples within 0–30 cm depth in each plot. The two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…This aligns with regenerative agriculture practices that prioritize watershed health [139]. Onion Grass biochar 0.5 kg/m 2 Boost in onion yield [150] Carrot Wood biochar 0 to 20 t/acre Positive impact on carrot weight [151] Studies indicate that the incorporation of biochar into agricultural soils can enhance crop yields. Its impact on nutrient availability, water retention, and soil structure contributes to increased productivity.…”
Section: Biochar and Regenerative Agriculturementioning
confidence: 81%
“…This aligns with regenerative agriculture practices that prioritize watershed health [139]. Onion Grass biochar 0.5 kg/m 2 Boost in onion yield [150] Carrot Wood biochar 0 to 20 t/acre Positive impact on carrot weight [151] Studies indicate that the incorporation of biochar into agricultural soils can enhance crop yields. Its impact on nutrient availability, water retention, and soil structure contributes to increased productivity.…”
Section: Biochar and Regenerative Agriculturementioning
confidence: 81%
“…Talwar Dilpreet et al (2017) 75% of suggested dose of NPK (suggested dose of Nitrogen, Phosphorus, Potassium and Sulphur for onion crop is 100:50:100:60 kg/ha)+ 5t/ha poultry manure and Phosphorous solubilizing bacteria and Azospirillum inoculation improved the nutrient availability and increased the photosynthesis rate, thereby increasing the quality parameters (nitrogen, phosphorus, potassium, sulfur, soluble solids, and allyl propyl disulfide content in the bulb) and yield attributes (Mahala et al, 2018) 1/3 rd of recommended nitrogen through farmyard manure + vermicompost + neem cake + biofertilizer containing nitrogen and phosphorous carriers. Better onion bulb yield and high production efficiency (Narkhede et al (2017) Complete dose of NPK fertilizers (125, 32.7 and 50 kg/ha) + vermicompost @ 25 t/ha onion production and good soil fertility management under the subtropical zone of Jammu (Gupta et al, 2019) Grass biochar (0.5 kg/m 2 ) combined with inorganic fertilizer (150kg/ha urea and 100 kg/ha Di Ammonium Phosphate appliedas soil application) increased soil nitrogen accumulation, improved soil properties, and high marketable bulb yield Aneseyee and Tekilil Wolde (2021).…”
Section: Integrated Nutrient Management Approaches In Onionmentioning
confidence: 99%
“…Combined biochar with NPK increased cucumber production, nutritional contents of cucumber fruit [128]. The biochar of grass and inorganic fertiliser application significantly shows increase in marketable bulb yield of onion [129]. The influence of biochar on the development of oil palm and rubber seedlings might aid in field replanting by boosting growth [130].…”
Section: Effect Of Biochar Application On Crop Yieldmentioning
confidence: 99%